Rayleigh laser guide star calibration unit for the Large Binocular Telescope - Schwab, Christian; Rakich, Andrew (Applied optics, 2010)
We describe the calibration method to be used for the off-axis laser guide stars at the Large Binocular Telescope’s (LBT’s) advanced Rayleigh guided ground layer adaptive optics system facility and the optical design of a dedicated calibration unit. Several possible solutions for generating artificial stars with the same wavefront as the real beacons were investigated. We find the use of a computer-generated hologram to be the best solution to the problem of producing aberrated light exactly matching that delivered by the primary mirror of the telescope. A detailed design and tolerance analysis is complete and the project is currently moving into the fabrication phase.